2015
DOI: 10.1111/evj.12444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic appearance of normal and injured lateral patellar ligaments in the equine stifle

Abstract: Normal variations in shape, echogenicity and fibre pattern of the LPL are important considerations to prevent false positive diagnoses during ultrasonography. LPL injuries were often severe and associated with craniolateral stifle trauma. Prognosis varied from good to guarded in horses without additional severe injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…The majority of horses presented with mild to moderate, chronic hind limb lameness that had been previously treated. In this study, IPL injury was rarely associated with trauma, which differs from lateral patellar ligament injury presentation . Presenting lameness scores were not significantly different between horses classified as having a predominant IA injury compared to those classified with a predominant IPL injury, suggesting that the degree of lameness does not correlate with specific injury type.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The majority of horses presented with mild to moderate, chronic hind limb lameness that had been previously treated. In this study, IPL injury was rarely associated with trauma, which differs from lateral patellar ligament injury presentation . Presenting lameness scores were not significantly different between horses classified as having a predominant IA injury compared to those classified with a predominant IPL injury, suggesting that the degree of lameness does not correlate with specific injury type.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, IPL injury was rarely associated with trauma, which differs from lateral patellar ligament injury presentation. 10 Presenting lameness scores were not significantly different between horses classified as having a predominant IA injury compared to those classified with a predominant IPL injury, suggesting that the degree of lameness does not correlate with specific injury type. Previous reports of IPL desmopathy have indicated a poor response to IA stifle analgesia.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Eight of these papers stated that 'there was no history of tendon injury', three papers stated 'no history of orthopaedic disease'. In two papers regarding patellar ligament desmitis the criterion was 'no history of stifle lameness', 27,28 and in one paper the definition of history was a statement that there was 'no unexplained absence from racing for longer than one year'. The number of methods stated in each study varied between 0 and 5, with a median of three.…”
Section: Desmitis/tendinitismentioning
confidence: 99%
“…The study identified normal variations in shape, echogenicity and fibre pattern in the normal LPL. Injuries to the LPL were often severe and associated with trauma, and had a very variable prognosis . While novel imaging methods are being increasingly used, radiography still remains the imaging modality most frequently used to image the equine stifle.…”
mentioning
confidence: 99%